SUPLEMENTASI CRUDE ENZIM PAPAIN DALAM PAKAN PEMBESARAN IKAN BERONANG, Siganus guttatus - Usman Usman; Asda Laining; Erik Sutikno (Universitas Gadjah Mada, 2014)
In intensive ﬁ sh farming, feed costs can reach up to 70% of the total cost production, so that its efﬁ ciency needs to be improved. The aims of this study were to improve ﬁ sh growth rate and feed efﬁ ciency for rabbit ﬁ sh grow-out through supplementation of crude papain enzyme in the feed. Test ﬁ sh were juvenile of rabbitﬁ sh, Siganus guttatus, with average initial weight of 40±3.5 g. Fish were stocked in 12 of 1×1×2 m3 ﬂ oating net cages with density of 16 ﬁ sh/cage. As dietary treatments were different dosages of crude papain enzyme namely (A) 0%, (B) 0.0125%, (C) 0.025%, and (D) 0.050%. The rabbitﬁ sh were fed to satiation in the morning and afternoon for 120 days. The results showed that speciﬁ c growth rate, survival rate of the ﬁ sh, feed efﬁ ciency, protein efﬁ ciency ratio, and the level of feed intake were not signiﬁ cantly different (P>0.05) among treatments. However, there was a tendency that increasing of supplementation level of crude papain enzyme in diets, ﬁ sh growth rate, feed efﬁ ciency, and protein efﬁ ciency ratio also increased.